Approximation of derivations on proper JCQ*-algebras - Kim, Soo Hwan (JOURNAL OF ADVANCES IN PHYSICS, 2015)
In this paper, we prove the generalized Hyers-Ulam stability of proper JCQ*-derivations on JCQ*-triples associated to the general (m,n)-Cauchy-Jensen additive functional equation.